Isotopic and Hydrogeochemical Characteristics and Genesis of Warm Springs in the Jiangcang Basin, Qinghai, China - Liu, Lingxia; Qi, Shihua; Zhang, Yongbin; Gao, Ming; Hu, Jing; Wang, Wenzhong (Frontiers in Earth Science, 2022)
The Jiangcang Basin is a Cenozoic faulted basin, where many low-temperature warm springs with the highest temperature of 36.6℃ are exposed. The study of the hydrogeochemical characteristics of the geothermal fluids of these warm springs can effectively reveal the genetic mechanisms of geothermal resources in the Jiangcang Basin and thus is greatly significant for the development and utilization of geothermal resources in Qinghai Province. Based on the geothermal geological conditions of the Jiangcang Basin, this study analyzed the hydrochemical and isotopic characteristics of water samples collected from cold water and four warm springs in the Jiangcang Basin, obtaining the following results. The four warm springs have hydrochemical types of HCO3-Ca·Mg, HCO3-Ca·Na·Mg, and HCO3·SO4-Na·Ca and total dissolved solids (TDS) of 720.4‒1663 mg /L. Moreover, there is no significant positive correlation between Cl- and other ions in the warm springs. The isotopic analysis results show that the warm springs are mainly recharged by atmospheric precipitation and the meltwater from ice and snow, with a recharge elevation of 4401‒4501 m. Furthermore, the geothermal reservoirs in the Jiangcang Basin have temperatures of 51‒83 ℃ and circulation depths of 1848‒2610 m. The atmospheric precipitation and the meltwater from ice and snow infiltrate downward in high mountain areas and then form runoffs along the tectonic channels in the basin. After being heated through deep circulation, they migrate upward along fault fracture zones under the influence of faults and the water blocking of mudstones, during which they cool through thermal conduction and mixing with the shallow cold groundwater. Finally, the mixed water is exposed in the form of low-temperature tectonic warm springs. The results of this study can provide data for the exploitation and utilization of geothermal resources in Qinghai Province.